The evaluation by criteria in Secondary Education - Morales Sánchez, José Víctor (Avances en Supervisión Educativa, 2013)
When the Spanish educational system moved its focus regarding the evaluation in Secondary Education from the contents to the criteria, not few teachers found it difficult to adapt to the new method. This step, a triple somersault for some, demands a new structure, a different way of matching objectives, contents, criteria, competences, procedures, instruments, etc. There is a double difficulty. On the one hand, the teaching training received at university by a great number of secondary school teachers is quite far from these new methods. Consequently, there is a conceptual difficulty, it is hard for them to understand this new way, to learn how to apply it and to envisage its effectiveness. On the other hand, once you have understood and assimilated this concept, to establish this new structure demands a remarkable amount of time and coordination on the part of the members of every department, but time is not something we teachers have to spare these days. This article aims at offering help to those secondary school teachers buried in the task of adapting themselves to the requirement of taking the criteria as the basis of learning evaluation, in order to make it easier to conceive the new system and, in some way, to guide them along the process hard process of building up this structure.